2018
DOI: 10.1159/000486621
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Reserve Hypothesis in Frontotemporal Dementia: Evidence from a Brain SPECT Study in a Series of Greek Frontotemporal Dementia Patients

Abstract: Background and Objective: Cognitive reserve (CR) mediates the clinical expression of brain pathology in Alzheimer’s disease, while there are much less relevant data in frontotemporal dementia (FTD). In the present study we examined whether CR, measured using the Cognitive Reserve Index (CRI), correlated with regional cerebral blood flow (rCBF) in Greek FTD patients. Methods: Eighty FTD patients, i.e., 47 with behavioral variant FTD (bvFTD) and 33 with primary progressive aphasia (PPA), were enrolled into this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 33 publications
2
19
0
4
Order By: Relevance
“…In Multiple Sclerosis (MS) patients, Fenu et al [38] showed a significant association between the Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS) and the interaction between CRIq scores and cortical gray matter volume, adjusted for age and disability (p = 0.004, no effect estimates reported). In patients with frontotemporal dementia, Maiovis et al [39] found that higher total CRIq, CRIq -Leisure Time, and CRIq-Education scores were associated with lower regional cerebral blood flow (rCBF) in the bilateral frontal and left temporal cortex (e.g. association between the CRIq total score and the left frontal rCBF for the behavioral variant frontotemporal dementia group (F = 3.7, p = 0.008) and for the primary progressive aphasia group (F = 4.502, p = 0.004).…”
Section: Resultsmentioning
confidence: 99%
“…In Multiple Sclerosis (MS) patients, Fenu et al [38] showed a significant association between the Brief International Cognitive Assessment for Multiple Sclerosis (BICAMS) and the interaction between CRIq scores and cortical gray matter volume, adjusted for age and disability (p = 0.004, no effect estimates reported). In patients with frontotemporal dementia, Maiovis et al [39] found that higher total CRIq, CRIq -Leisure Time, and CRIq-Education scores were associated with lower regional cerebral blood flow (rCBF) in the bilateral frontal and left temporal cortex (e.g. association between the CRIq total score and the left frontal rCBF for the behavioral variant frontotemporal dementia group (F = 3.7, p = 0.008) and for the primary progressive aphasia group (F = 4.502, p = 0.004).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, it is important to consider that the CRIq is not the only tool that can be used to obtain a lifeexperience proxy of CR (see for example Altieri et al, 2018;Leoń, Garciá-García, & Roldań-Tapia, 2014;Valenzuela & Sachdev, 2007); other questionnaires or scales may even outperform the predictive performance of CRIq (Kartschmit, Mikolajczyk, Schubert, & Lacruz, 2019) and in turn, the accuracy of calculated cut-offs. We used the CRIq since it is a validated and versatile instrument that has been widely used for estimating CR in some previous researches (Artemiadis et al, 2020;Lavrencic et al, 2018;Lee et al, 2019;Maiovis et al, 2018;Ozakbas et al, 2021). Here, for the rst time, we show how it can be used to build more accurate normative data for clinical uses.…”
Section: Limitations and Further Implicationsmentioning
confidence: 99%
“…The Cognitive Reserve Index questionnaire (CRIq, Nucci, Mapelli, & Mondini, 2012) allows to estimate CR from education, occupational activity, and leisure-time activity as they concur in building up the reserve (Chan et al, 2018;Livingston et al, 2017;Scarmeas & Stern, 2003;Ward et al, 2015). The CRIq is translated into many languages and it has been used both for clinical and research purposes (Artemiadis et al, 2020;Lavrencic et al, 2018;Lee et al, 2019;Maiovis, Ioannidis, Gerasimou, Gotzamani-Psarrakou, & Karacostas, 2018;Montemurro, Jarema, & Mondini, 2021;Ozakbas et al, 2021). It has been also shown that, when using CRIq, the effect of CR signi cantly interacts with age in the expected cognitive performance (Montemurro, Mondini, & Arcara, 2021); in particular, as age increases performance is typically worse, but not when CRIq score is high.…”
Section: Introductionmentioning
confidence: 99%
“…The Cognitive Reserve Index questionnaire (CRIq, Nucci, Mapelli, & Mondini, 2012) allows to estimate CR from education, occupational activity, and leisure-time activity as they concur in building up the reserve (Chan et al, 2018;Livingston et al, 2017;Scarmeas & Stern, 2003;Ward et al, 2015). The CRIq is translated into many languages and it has been used both for clinical and research purposes (Artemiadis et al, 2020;Lavrencic et al, 2018;Lee et al, 2019;Maiovis, Ioannidis, Gerasimou, Gotzamani-Psarrakou, & Karacostas, 2018;Montemurro, Jarema, & Mondini, 2021;Ozakbas et al, 2021). It has been also shown that, when using CRIq, the effect of CR signi cantly interacts with age in the expected cognitive performance (Montemurro, Mondini, & Arcara, 2021); in particular, as age increases performance is typically worse, but not when CRIq score is high.…”
Section: Introductionmentioning
confidence: 99%